Capacity Building for HRD Trainers through NotebookLM-Based AI Literacy Training in Jakarta - Teguh Iman Santoso (SOCIRCLE : Journal Of Social Community Services, 2026)
The rapid advancement of artificial intelligence (AI) has reshaped professional education and training, requiring trainers, lecturers, and teachers to develop practical digital competencies for instructional innovation. This community service activity aimed to optimize the use of NotebookLM among members of the National Association of HRD Trainers by strengthening participants’ ability to apply AI tools for source-based learning, material development, and professional training design. The activity was conducted as a half-day participatory workshop on Sunday, April 26, 2026, at Hotel Sofyan Cut Meutia, Central Jakarta. The workshop involved members of the National Association of HRD Trainers with professional backgrounds in training, education, and human resource development. The implementation combined theoretical framing, live demonstrations, guided practice, scenario-based simulations, and reflective evaluation. The results showed that participants were able to operate NotebookLM’s core features, including uploading learning sources, generating summaries, preparing study guides, developing quizzes, creating discussion prompts, and conducting source-grounded question-and-answer activities. The workshop also produced practical outputs in the form of AI-assisted summaries, training guides, quiz drafts, and learning prompts that could be adapted for professional training contexts. Participants demonstrated improved confidence in using NotebookLM and showed greater awareness of ethical AI use, source validation, and the importance of human judgment in AI-assisted instructional design. These findings indicate that practice-oriented NotebookLM training can strengthen digital literacy and support more interactive, adaptive, and source-grounded training practices.